Cross-sectional study of major procedure codes among hospitalized patients with traumatic brain injury by level of injury severity in the 2004 to 2014 Nationwide Inpatient Sample. Issue 6 (12th February 2021) - Beydoun, Hind A.; Butt, Catherine; Beydoun, May A.; Hossain, Sharmin; Eid, Shaker M.; Zonderman, Alan B.
Abstract : Abstract: Despite its public health significance, TBI management across US healthcare institutions and patient characteristics with an emphasis on utilization and outcomes of TBI-specific procedures have not been evaluated at the national level. We aimed to characterize top 10 procedure codes among hospitalized adults with TBI as primary diagnosis by injury severity. A Cross-sectional study was conducted using 546, 548 hospitalization records from the 2004 to 2014 Nationwide Inpatient Sample were analyzed. Data elements of interest included injury, patient, hospital characteristics, procedures, in-hospital death and length of stay. Ten top procedure codes were "Closure of skin and subcutaneous tissue of other sites", "Insertion of endotracheal tube", "Continuous invasive mechanical ventilation for less than 96 consecutive hours", "Venous catheterization (not elsewhere classified)", "Continuous invasive mechanical ventilation for 96 consecutive hours or more", "Transfusion of packed cells", "Incision of cerebral meninges", "Serum transfusion (not elsewhere classified)", "Temporary tracheostomy", and "Arterial catherization". Prevalence rates ranged between 3.1% and 15.5%, with variations according to injury severity and over time. Whereas "Closure of skin and subcutaneous tissue of other sites" was associated with fewer in-hospital deaths and shorter hospitalizations, "Temporary tracheostomy" was associated with fewer in-hospital deaths among moderate-to-severe TBI patients, and "Continuous invasive mechanical ventilation for less than 96 consecutive hours" was associated with shorter hospitalizations among severe TBI patients. Other procedures were associated with worse outcomes. Nationwide, the most frequently reported hospitalization procedure codes among TBI patients aimed at homeostatic stabilization and differed in prevalence, trends, and outcomes according to injury severity. Abstract : Supplemental Digital Content is available in the text